Removal And Recovery Of Copper From Electroplating Rinse Water Via A Galvanic Cementation System - Hor, Yean Phin (2003)

(untitled)
Suatu sistem galvani yang menggunakan sel alir telah diperkenalkan dalam penyingkiran kuprum dalam air buangan. Penyelidikan ini menilai keupayaan proses penyimenan galvani dalam menyingkirkan kuprum dari air buangan industri pengelektrosaduran di samping memperoleh semula logam kuprum. Proses ini tidak memerlukan bekalan tenaga luar kerana pertukaran kimia antara gandingan kuprum/ferum berlaku secara spontan. A galvanic system for the removal of copper from aqueous solutions using a divided flow-through cell is proposed. The present study looks into the feasibility of removing copper from dilute electroplating rinse water and recovering it in metallic form by a galvanic cementation process. This process does not require an external supply of energy due to the spontaneous chemical reaction between the copper/iron couple.